The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/gerona/60.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Association Between Antihypertensive Medications and Cognitive Impairment in an Elderly Population

Abstract: Antihypertensive use, particularly diuretics, angiotensin-converting enzymes inhibitors, beta-blockers, and angiotensin receptor blockers, may be associated with a lower rate of cognitive decline in older adults, including those with AD. Until a randomized clinical trial confirms our results, findings of this observational study should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 36 publications
2
51
0
4
Order By: Relevance
“…This is consistent with clinical findings of lower dementia risk in subjects with persistent elevated BP, despite antihypertensive treatments. 19,29 Furthermore, these results, consistent with the Honolulu Asia Aging Study (HAAS) and Rotterdam findings, 13,14 provide a neuropathologic basis to support the clinical 18,20 and population studies 4,[15][16][17]19 that found significant reductions in dementia and AD risk in persons treated with antihypertensive medications. Antiamyloidogenic and neuroprotective effects of the antihypertensive drug valsartan were reported in the Tg2576 AD mouse model, even at a dose corresponding to half the lowest recommended dose for HTN treatment in humans, 33 providing evidence that at least some antihypertensive medications can directly affect biologic processes involved in AD.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…This is consistent with clinical findings of lower dementia risk in subjects with persistent elevated BP, despite antihypertensive treatments. 19,29 Furthermore, these results, consistent with the Honolulu Asia Aging Study (HAAS) and Rotterdam findings, 13,14 provide a neuropathologic basis to support the clinical 18,20 and population studies 4,[15][16][17]19 that found significant reductions in dementia and AD risk in persons treated with antihypertensive medications. Antiamyloidogenic and neuroprotective effects of the antihypertensive drug valsartan were reported in the Tg2576 AD mouse model, even at a dose corresponding to half the lowest recommended dose for HTN treatment in humans, 33 providing evidence that at least some antihypertensive medications can directly affect biologic processes involved in AD.…”
Section: Resultssupporting
confidence: 58%
“…Antihypertensive treatments have been associated with lower incidence of clinically diagnosed AD and better cognitive function [15][16][17] ; similarly, treatment of hypertensive subjects was associated with lower dementia risk. [18][19][20] However, the specific classes of anti-HTN medication Editorial,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In a retrospective analysis, lower rates of cognitive decline were observed with diuretic, ACE inhibitor, and BB use in the elderly, and improved cognition was seen with angiotensin receptor blockers (ARB). 17 Another retrospective, casecontrol study showed decreased odds of dementia with BB use during the preceding 3 years. 19 However, a small, 6-year follow-up study suggested worse cognitive decline among those with BB and ACE inhibitor use, and improved cognition with calcium channel blocker use in the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Limited data from observational studies suggest that BB use may slow cognitive decline 17,18 and possibly prevent dementia, 19 while others have found divergent results. 20 The current study examines the association between antihypertensive drug class and the risk of cognitive impairment in a large prospective cohort of elderly Japanese American men.…”
mentioning
confidence: 99%